Anthropogenic disturbances affect the interactions between ants and fleshy fruits in two neotropical biodiversity hotspots - Oliveira, Paulo S.; Christianini, Alexander V.; Bieber, Ana G. D.; Pizo, Marco A. [UNESP] (Cambridge University Press (CUP), 2017)
Introduction The main ecological function of fleshy fruits is probably advertisement, such that they look or smell attractive enough to entice a particular type of animal (frugivore) to eat them (Schaefer & Ruxton, 2011). By feeding on the nutritious fleshy portion of fruits and seeds (pericarp, pulp, aril), mobile frugivores frequently detach them from the parent plant and deposit the seeds someplace else. As such, seed dispersal is essentially a mutualism in which nutrition of a frugivore is exchanged for mobility of a plant's offspring (Jordano, 2000). The tropical region not only harbours a great diversity of plant and animal species, but also contains a huge variety of fruit traits (colour, morphology and chemistry) associated with many types of seed dispersal strategies (e.g. Galetti et al., 2011). Seed dispersal by animals clearly predominates, and it is estimated that nearly 90 per cent of tropical forest eudicots have fleshy fruits/seeds (i.e. diaspores, sensu van der Pijl, 1969) that rely on vertebrate frugivores for dissemination (Fleming et al., 1987; Levey et al., 1994). Individual plant species, however, are rarely adapted to seed dispersal by only one particular species of frugivore (Howe & Smallwood, 1982). Indeed, because most plant species are involved with numerous dispersers, a clear picture of the seed rain of a given plant species frequently entails understanding seed movements mediated by dispersal agents not only from multiple animal species, but also from several animal groups as well (e.g. Vander Wall & Longland, 2005). Detailed field observations of animal behaviour and seed fate have made increasingly apparent that seed movements can involve sequential steps, each performed by a distinct dispersal agent, in a process known as diplochory or two-phase dispersal (Vander Wall & Longland, 2005). Phase one dispersal refers to the initial movement of the seed away from the parent plant, which can result in avoidance of density-dependent seed and seedling mortality near the parent (Janzen, 1970). Phase two often involves subsequent seed movements that may result in seed deposition in predictable, favourable microsites where seedling establishment is increased (i.e. directed dispersal). Two-phase dispersal systems can be regarded as special cases of secondary dispersal, which deserve special attention since they combine two dispersal modes that can offer more benefits to plants (Vander Wall & Longland, 2005; Camargo et al., 2016).